Optimized Technical and Economic Evaluation of the Connection Point of Distributed Generators - Neri Pereira, Milton Luiz; Padilha-Feltrin, Antonio [UNESP]; Rueda-Medina, Augusto C. [UNESP] (Springer, 2015)
In most studies, the problem of allocation and sizing of the distributed generation is addressed considering that the distributed generators (DGs) could be installed in any bus of the system. Thus, these studies bring the optimal or best allocation place for the DGs without considering that in a real implementation not all buses are valid candidates due to restrictions in the system, such as environmental, social, and geographical aspects, for example. In this sense, the problem treated in this work consists of evaluating the allocating point of DGs in distribution systems based on technical and economic aspects, assuming that they are not necessarily located near the optimal or best allocation bus of the system. Two interests are investigated: on one hand, the problem 1, formulated as a multi-objective optimization (MO) problem and defined from the point of view of the independent energy producer (IEP) which owns the DGs; and, on the other hand, the problem 2, also formulated as a MO problem, but defined from the point of view of the distribution system operator (DSO). The results for the two problems were a set of solutions that established a conflict between the IEP and the DSO because the alternative that proved the most promising for the IEP was the less attractive for the DSO. The set of solutions found through the used solution technique constitutes a flexible environment that allows the IEP and the DSO to evaluate each proposed solution and decide on the one that is closest to the interests of both parties.
Keywords: Distributed generation; Electric distribution system; Multi-objective optimization